Tingkat Adopsi Teknologi Budi Daya Jagung Hibrida Pada Agroekosistem Lahan Kering - Saptana, Saptana; Purwantini, Tri Bastuti; Rachmita, Annisa Rika (Jurnal Penelitian Pertanian Tanaman Pangan, 2018)
The commodity of corn is an important of food crop that have a strategic role in the agricultural development of Indonesia. In the last two decade the national corn demand had continued increasing, especially using main materials of feed industries. The program of hybrid corn development should be increasing by to achieve self sufficient continue of corn. Beside that adoption of technology innovation of farmers level became important factors of farming successful in the increasing productivity and farmer income. The research was conducted at three location of Patanas village, there are Paccarammengan (South Sulawesi), Sindang Mekar (West Java) and Resongo (East Java) in 2017 with using the survey method. Primary data was collected through interview with 66 farmers as the respondents by giving a structured questionnares. The data were arranged in a cross tabulation and analyzed to measure the feasibility of the farming based on the gross B/C ratio, profitability and BEP (Break Even Point) production. The result showed that corn farming in the research area was profitable with gross value of B/C 3.06 - 3.18 without rent land and 1.77 - 1.98 with rent land.